1987
DOI: 10.2220/biomedres.8.269
|View full text |Cite
|
Sign up to set email alerts
|

<b>SCANNING ELECTRON MICROSCOPE OBSERVATION OF PENILE VASCULAR CASTS IN THE DOG: AN INQUIRY INTO THE POSSIBLE MECHANISM OF ERECTION BASED ON THE </b><b>FINDINGS </b>

Abstract: The vascular construction of the dog penis was investigated mainly by scanning electron microscopic observation of corrosion casts produced by injection of methylmethacrylate into the penile artery and its branches. The corpus cavernosum penis was supplied mainly by the penile deep artery; only its distal end received a few small branches from the dorsal artery. The helicine arteries were provided with polsters which protruded into the lumen so prominently that they might conspicuously reduce the lurninal spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In a previous pressure study, the pressure of the internal pudendal artery was measured as a useful param eter to estimate the hemodynamics in erection [ 15], Re cent morphological studies have shown that the deep artery, one of the major branches of the internal pudendal artery, mainly supplies the corpus cavernosum in dogs as well as in humans [14,16,17], The selective measurement of the deep arterial pressure is therefore considered to be a direct indicator for clarifying the hemodynamics of penile erection.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous pressure study, the pressure of the internal pudendal artery was measured as a useful param eter to estimate the hemodynamics in erection [ 15], Re cent morphological studies have shown that the deep artery, one of the major branches of the internal pudendal artery, mainly supplies the corpus cavernosum in dogs as well as in humans [14,16,17], The selective measurement of the deep arterial pressure is therefore considered to be a direct indicator for clarifying the hemodynamics of penile erection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Stieve [9] claimed that such a compression was an artificial and distorted figure. Conti [10] and Goldstein et al [11] attributed the restriction of the venous outflow to the contraction of polsters in the veins of the penis, although we dispute the existence of venous polsters at least in the dog penis [4,7], In a previous study [4], we produced vascular corro sion casts of dog CCP in flaccid, erect and rigid states, and revealed under the scanning electron microscope that the venous occlusion during the erect and rigid states occurred in both the postcavemous venules and the penetrating veins. We further determined that the deep artery passing through the tunica albuginea was occluded during the rigid state to prevent any backflow of blood from the cavernous sinuses [4], In the present study, we carried out light-microscopic observation of dog penile blood vessels in order to clarify the mecha nism of such vascular occlusions.…”
Section: Discussionmentioning
confidence: 92%
“…(1) Vasoactive intestinal polypeptide involved in vasodi latation has been shown to be abundantly present in the cavernous tissues of the penis and to be localized in neu ral elements [12]. Vasoactive intestinal polypeptide-con taining nerves were densely distributed in smooth mus cles dispersed in cavernous trabeculae as well as in those of helicine arteries [7,12]. Papaverine, a relaxant of smooth muscles, induces erection; it has also been dem onstrated to cause restricted venous outflow from cav ernous sinuses [3,4], These data suggest that the relax ation of trabecular smooth muscles may be important for erection, probably as the cause of the restriction of venous outflow as well as the vasodilatation of the heli cine arteries, which gives rapid inflow with high pressure to the cavernous sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9] or perforating veins [10] and postcavernous ven ules [5,8,9] which connect the cavernous sinuses with the penetrating vein showed a wide lumen in the flaccid state ( fig. 4a, 5a).…”
Section: Histological Examinationmentioning
confidence: 99%